Youth's personal relationships, psychological symptoms, and the use of different substances: A population-based study. Issue 3 (June 2022) - del Palacio-Gonzalez, Adriana; Pedersen, Mads Uffe
Background: Externalising symptoms and peer influence are well-established predictors of youth's substance use in general. However, there is little integrative research that compares the relative contribution of psychological and social relationship characteristics as predictors of the use of specific substances among youth in different developmental stages.Methods: A representative sample of Danish adolescents ( n = 1, 168) and emerging adults (EA; n = 1, 878) reported last-month prevalence use of cigarettes, cannabis, and other illicit drugs (OID), and four indices of alcohol use. Predictor variables included internalising and externalising symptoms, and major characteristics of the youth's relationships (e.g., parental drug use, number of close friends).Results: Having a close friend who used illicit drugs, and high externalising symptoms, predicted the risk for using all substances across both age groups. Alcohol use was more consistently related to peer-related variables than to symptoms. Smoking cigarettes, cannabis use, and OIDs use were related to peer and symptom variables. Age group moderated some associations. Parental separation was related more strongly to alcohol use among adolescents than among EA, and higher internalising symptoms were more strongly related to smoking and using OIDs among adolescents than among EA. Male EAs had higher risk for using alcohol than female EAs.Conclusion: Beyond having a close friend who used illicit drugs, and externalising problems, the use of each substance was better explained by a different group of variables. There were few but important moderations by age group. The findings highlight the need for research on risk factors for substance use that is developmentally sensitive, particularly for adolescents, and for specific substances. Thus, interventions and policies should address social, developmental, and psychological factors.